Digitally Programmable Partially Active-R Sinusoidal Oscillators - Muhammad Taher Abuelma'atti; Abdulrahman Khalaf Al-Ali; Sami Saud Buhalim; Syed Tauseef Ahmed (Active and Passive Electronic Components)
New, simple sinusoidal oscillator circuits are proposed. Each circuit uses an internally compensated operational amplifier, a resistor, and a capacitor. The feasibility of obtaining digitally programmable sinusoidal oscillation is studied and a new digitally programmable capacitorless resistorless sinusoidal oscillator is developed.